A likelihood control chart for monitoring bivariate lifetime processes - Zainab Abbasi Ganji; Bahram Sadeghpour Gildeh (Journal of Mahani Mathematical Research, 2022)
In this survey, two new control charts CCLR and CCALR for bivariate exponential variables by dependence structure based on Farlie-Gumbel-Morgenstern copula model are introduced. Simulation study is done to make a comparison between two proposed control charts in terms of average run length (ARL). Results show that the CCALR performs better than CCLR. Anumerical example is provided to fortify the theoretical findings.